INTERACTIONS OF THE (001) SURFACE OF MUSCOVITE WITH CU(II), ZN(II), AND CD(II): A COMPUTER SIMULATION STUDY - A COMPUTER SIMULATION STUDY - Steele H.M.; Wright K.; Nygren M.A.; Hillier I.H. (My University, 2000)
Toxic metal ions can bind to the surface of minerals in a number of ways including chemisorption, physisorption, precipitation, and cation exchange. We have used atomistic simulation techniques and a set of specific interatomic potentials to describe the non-Coulombic interactions between three widely found heavy metal contaminants and the surface of muscovite mica. The binding of Cu(II), Zn(II), and Cd(II) ions to the smooth (001) basal plane of muscovite mica and to a surface containing defects was considered for both a hydrated and nonhydrated system. The results of these simulations show that no strong bonds are formed with the smooth basal plane by any of the three cations considered. However, on the introduction of edge-like defects, the Cu(II) and Zn(II) cations bound strongly to the defect sites with all bond lengths and coordination numbers in good agreement with experiment, whereas Cd binding remained unfavorable.